Exploring possible strategies for treating SARS-CoV-2 in sewage wastewater: A review of current research and future directions - Peerzada Gh Jeelani; Syed Muzammil Munawar; S. Khaleel Basha; Gopi Krishna P; Bruce Joshua Sinclair; A Dharshini Jenifer; Nupur Ojha; Abdel-Tawab Mossa; Ramalingam Chidambaram (Hygiene and Environmental Health Advances, 2023)
The advent of acute respiratory coronavirus disease (COVID-19) is convoyed by the shedding of the virus in stool. Although inhalation from person-to-person and aerosol/droplet transmission are the main modes of SARS-Coronavirus-2 (SARS-CoV-2) transmission, currently available evidence indicates the presence of viral RNA in the sewerage wastewater, which highlights the need for more effective corona virus treatment options. In the existing COVID-19 pandemic, a substantial percentage of cases shed SARS-CoV-2 viral RNA in their faeces. Hence the treating this sewerage wastewater with proper surveillance is essential to contain this deadly pathogen from further transmission. Since, the viral disinfectants will not be very effective on sewerage waste as organic matter, and suspended solids in water can protect viruses that adsorb to these particles. More effective methods and measures are needed to prevent this virus from spreading. This review will explore some potential methods to treat the SARS-CoV-2 infected sewerage wastewater, current research and future directions.